2017
DOI: 10.4238/gmr16019522
|View full text |Cite
|
Sign up to set email alerts
|

SNP detection using RNA-sequences of candidate genes associated with puberty in cattle

Abstract: ABSTRACT. Fertility traits, such as heifer pregnancy, are economically important in cattle production systems, and are therefore, used in genetic selection programs. The aim of this study was to identify single nucleotide polymorphisms (SNPs) using RNA-sequencing (RNA-Seq) data from ovary, uterus, endometrium, pituitary gland, hypothalamus, liver, longissimus dorsi muscle, and adipose tissue in 62 candidate genes associated with heifer puberty in cattle. RNA-Seq reads were assembled to the bovine reference gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Such a large geographic distribution may be consistent with known ancient migration and admixture events during dispersal of cattle out of the domestication center [17,18,20,[55][56][57][58][59][60][61] as well as more recent historical migrations between Asia and Europe and in the Mediterranean [27,62], although admixture phenomena among wild taurine and zebuine progenitors may not be ruled out. Interestingly, we found that several of the candidate genes on BTA14 (XKR4, TMEM68, TGS1, LYN, CHCHD7, SDR16C5, PENK, TOX, RPS20, PLAG1) had been previously reported to harbor signals of selection/association in taurine/zebuine composite populations or zebuine breeds [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. This evidence possibly supports the speculation that pigment-related gene variants and phenotypes in grey taurine cattle may represent a heritage of zebuine origin, despite the fact that, for PLAG1, an allele with major effects on body size, weight, and reproduction has been shown to be a >1000 year-old-derived allele that increased rapidly in frequency in Northwestern European B. taurus between the 16th and 18th centuries, and that was hence introgressed, towards the 19th and 20th centuries, into non-European B. taurus and Bos indicus breeds likely to increase the stature of modern cattle [79,80].…”
Section: Hair Greying: a Possible Zebuine Heritage In Taurine Cattle mentioning
confidence: 88%
“…Such a large geographic distribution may be consistent with known ancient migration and admixture events during dispersal of cattle out of the domestication center [17,18,20,[55][56][57][58][59][60][61] as well as more recent historical migrations between Asia and Europe and in the Mediterranean [27,62], although admixture phenomena among wild taurine and zebuine progenitors may not be ruled out. Interestingly, we found that several of the candidate genes on BTA14 (XKR4, TMEM68, TGS1, LYN, CHCHD7, SDR16C5, PENK, TOX, RPS20, PLAG1) had been previously reported to harbor signals of selection/association in taurine/zebuine composite populations or zebuine breeds [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. This evidence possibly supports the speculation that pigment-related gene variants and phenotypes in grey taurine cattle may represent a heritage of zebuine origin, despite the fact that, for PLAG1, an allele with major effects on body size, weight, and reproduction has been shown to be a >1000 year-old-derived allele that increased rapidly in frequency in Northwestern European B. taurus between the 16th and 18th centuries, and that was hence introgressed, towards the 19th and 20th centuries, into non-European B. taurus and Bos indicus breeds likely to increase the stature of modern cattle [79,80].…”
Section: Hair Greying: a Possible Zebuine Heritage In Taurine Cattle mentioning
confidence: 88%
“…(Table ). Additionally, seven out of 15 were overlapping with GWAS hits in other cattle populations, such as Brahman cattle (Bolormaa et al ; Fortes et al ), beef cattle (Dias et al ) and Holstein dairy cattle (Nayeri et al ) (Table ). Overall, we consider that the number of false‐positive results is small in our study.…”
Section: The Candidate Genes Are Associated With Heat Tolerance and Imentioning
confidence: 99%
“…The majority of selection signatures that we detected here are consistent with previous reports on selection signatures in Bangladesh zebu (Edea et al 2018 (Table 2). Additionally, seven out of 15 were overlapping with GWAS hits in other cattle populations, such as Brahman cattle (Bolormaa et al 2011;Fortes et al 2012), beef cattle (Dias et al 2017) and Holstein dairy cattle (Nayeri et al 2017) (Table 2). Overall, we consider that the number of false-positive results is small in our study.…”
mentioning
confidence: 99%
“…RNA-Seq experiments in livestock studies have identified significant SNPs in candidate genes associated with metabolic pathways that may play a role in the regulation of production traits [4,[8][9][10][11][12]. This has resulted in an improved understanding of the genetic architecture and a reduction in genome complexity of important traits such as feed efficiency, health, fertility, and meat quality traits in beef cattle [4,8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%